Pendidikan Islam dalam Konteks Makro dan Mikro: Implementasi Konsep dan Praktik di Pondok Pesantren Darunnajah Jakarta Selatan - Nazifah Husainah; Neni Handayani; Suharta; Najmi Ulya; Raspa Laa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Islamic education plays a strategic role in shaping students’ character, spiritual depth, and social competence. At the macro level, it is integrated into national policy frameworks, the formal education system, and broader challenges posed by globalization and modernization. At the micro level, Islamic education is realized through everyday practices within educational institutions, notably in pesantren. This study explores the implementation of Islamic education in the micro context of Pondok Pesantren Darunnajah Ulujami, South Jakarta, focusing on classroom learning, social interaction, and students’ daily life activities. Employing a qualitative approach with an exploratory case study design, data were collected through in-depth interviews, participatory observation, and document analysis. The study identifies five key themes: the alignment between national and local visions, the presence of transformational leadership, active community involvement, managerial innovation, and limitations in human resource capacity. The findings also highlight major challenges such as imbalanced curricula and organizational resistance to change. Nevertheless, the pesantren adopts effective strategies including continuous professional development, contextual curriculum development, and alumni engagement to strengthen institutional resilience. The study underscores the significance of integrating macro policy with micro-level implementation to build an adaptive, sustainable, and contextually relevant model of Islamic education that addresses both national goals and local realities.